Representation of Masculinity in Movie Captain America (The First Avenger) - Mohammad Raihan; Dhuha Hadiyansyah (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2024)
This study examines the representation of masculinity through the character of Steve Rogers in Captain America: The First Avenger (2011), focusing on his physical transformation, leadership, and self-sacrifice. Employing Charles Sanders Peirce’s semiotic theory and Janet Saltzman Chafetz’s framework of masculinity, the analysis explores how these theoretical perspectives illuminate the portrayal of masculinity in superhero narratives. The film highlights traditional masculine ideals such as physical strength, leadership, and moral integrity, while also presenting a more nuanced portrayal by integrating emotional vulnerability and intellectual capabilities into Rogers' character. The study suggests that Captain America both reflects historical gender norms and provides space for evolving conceptions of masculinity, offering new possibilities for gender representation in superhero films. This research contributes to understanding how superhero narratives shape societal perceptions of masculinity and challenges hegemonic ideals by depicting a more complex, multifaceted model of male identity.